Faktor-Faktor yang Mempengaruhi Anemia - Permata, Intan Indra; Achyar, Khamidah; Kusuma, Inggar Ratna (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Anemia is a condition in which the oxygen-carrying capacity of the blood is insufficient. Our previous study found that in Soreang Regency, which is a rural area, the prevalence of anemia among female students was 14.3%. The government is running an iron supplementation program to treat IDB in young people. This research uses a literature review. A literature search through journal publications in PubMed and also Google Scholar using the keywords